1998
DOI: 10.1172/jci551
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hair loss (alopecia areata) transferred by T lymphocytes to human scalp explants on SCID mice.

Abstract: Alopecia areata is a tissue-restricted autoimmune disease of the hair follicle, which results in hair loss and baldness. It is often psychologically devastating. The role of T lymphocytes in this disorder was investigated with cell transfer experiments. Scalp explants from patients were transplanted to severe combined immunodeficiency (SCID) mice and injected with autologous T lymphocytes isolated from involved scalp. T lymphocytes which had been cultured with hair follicle homogenate along with antigen-presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
189
3
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(203 citation statements)
references
References 22 publications
7
189
3
4
Order By: Relevance
“…IL-1R1 is known as a potent regulator of ICAM-1, 42 which in turn is implicated in regulation of adhesion and proliferation of skin lymphocytes and follicular keratinocytes 43,44 and is associated with some HF pathological conditions in humans, such as alopecia areata. 45,46 These results further support the idea that hairless mice are an attractive model for elucidating the molecular controls of normal and pathological catagen-associated DP movement.…”
Section: Discussionsupporting
confidence: 66%
“…IL-1R1 is known as a potent regulator of ICAM-1, 42 which in turn is implicated in regulation of adhesion and proliferation of skin lymphocytes and follicular keratinocytes 43,44 and is associated with some HF pathological conditions in humans, such as alopecia areata. 45,46 These results further support the idea that hairless mice are an attractive model for elucidating the molecular controls of normal and pathological catagen-associated DP movement.…”
Section: Discussionsupporting
confidence: 66%
“…3 Although the exact etiology of AA is still unknown, there is accumulated evidence that supports a hereditary susceptibility and an autoimmune pathogenesis, such as a familial history in 4-27%, 4,5 and the increased frequency of other autoimmune diseases, particularly autoimmune thyroid disease, and of organspecific autoantibodies in patients with AA [6][7][8] as well as the presence of CD8 + T cells next to the hair follicles. 9,10 Among the various immunomodulatory treatments that have been used to induce remission in AA, systemic corticosteroids have been administered in extensive or rapidly progressive AA and in alopecia totalis/universalis. 11,12 Systemic oral corticosteroids have been reported to be effective in extensive AA, but relapses occurred when the dosage was reduced.…”
Section: Introductionmentioning
confidence: 99%
“…T lymphocytes from the patients could cause alopecia areata, when cultured with hair follicle homogenate along with antigen-presenting cells and injected into the skin explants on severe combined immunodeficiency mice. 3 Purified T cell injection experiments result suggested that both CD4-and CD8-positive T cells have a role in pathogenesis of alopecia areata, CD8-positive cells acting as the main effector cells with the regulatory control by CD4-positive T cells. 4 This study was undertaken to clarify whether Th1 CD4 lymphocytes or Th2 CD4 lymphocytes are dominant in the lesions of patients with alopecia areata and also to elucidate the effect of cytokine therapy applying recombinant interleukin-4 (Il4) and neutralizing anti-interferon-ā„ (Ifng) antibody into the alopecia areata rodent model C3H/HeJ mice.…”
mentioning
confidence: 99%